2012
DOI: 10.1155/2012/802715
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-ASSR Interactions in Adults with Sensorineural Hearing Loss

Abstract: The multiple auditory steady-state response (multiple-ASSR) technique, where thresholds for up to 8 frequencies (4 in each ear) are obtained simultaneously, is currently of great interest for audiometric assessment of infants. Although threshold estimates using the multiple-ASSR appear to be reasonably accurate, it is not currently known whether it is more efficient to use multiple stimuli or single stimuli when testing individuals with sensorineural hearing loss (SNHL). The current study investigated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Simultaneous recording of monaural and binaural FFR could be beneficial for assessing binaural processing at the neural level (e.g., binaural interaction component). In consonance with findings of the present study, few investigations have demonstrated that auditory evoked potentials can be recorded from both ears simultaneously in the same recording using suitable stimulus presentation paradigms (Maruthy et al, 2019;John et al, 1998;Ishida & Stapells, 2012). Recently, Maruthy et al…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Simultaneous recording of monaural and binaural FFR could be beneficial for assessing binaural processing at the neural level (e.g., binaural interaction component). In consonance with findings of the present study, few investigations have demonstrated that auditory evoked potentials can be recorded from both ears simultaneously in the same recording using suitable stimulus presentation paradigms (Maruthy et al, 2019;John et al, 1998;Ishida & Stapells, 2012). Recently, Maruthy et al…”
Section: Discussionsupporting
confidence: 90%
“…Further, results showed that the click ABR of both ears obtained using novel stimulus paradigm was comparable to click ABR elicited using the conventional method. Ishida and Stapells (2012) recorded 40 Hz and 80 Hz ASSR using multiple stimuli presented simultaneously to one ear or both ears and showed that ASSR could be recorded from both ears simultaneously in the same recording. The amplitude of 80 Hz ASSR recorded by presenting multiple stimuli to both ears was similar to multiple stimuli to one ear condition.…”
Section: Discussionmentioning
confidence: 99%
“…11) were unexplained by the carrier spectrum. Higher stimulus levels lead to increased interactions, likely due to broader regions of activation in the cochlea (John et al 1998Ishida & Stapells 2012;McNerney & Burkard 2012). However, in contrast to the results seen in adults with normal hearing, the response amplitude for /i/ F1 decreases with further increase in stimulus bandwidth (response amplitude increased significantly from the LPF2k to LPF4k condition in normal hearing adults).…”
Section: Experiments Ii: Effect Of Bandwidthmentioning
confidence: 71%
“…Epochs with amplitudes exceeding 40 mV after bandpass filtering between 30 and 300 Hz were rejected, corresponding to values in the literature, ranging from approximately 30 to 60 mV. 20,42 The remaining epochs were pooled for further analysis, which are addressed as raw epochs in the remainder of this article.…”
Section: Preprocessing Proceduresmentioning
confidence: 99%